Weekly Biological Variation of Urine Protein Creatinine Ratio and Urine Specific Gravity in Healthy Dogs - Yanick Couture; Deborah Keys; Stacie Summers (Journal of Veterinary Internal Medicine)
ABSTRACT Background Urine protein‐creatinine ratio (UPC) and urine specific gravity (USG) are important measurements in the determination of renal proteinuria and chronic kidney disease. Biological and analytical variation estimates of these analytes to calculate the index of individuality (IoI) and a reference change value (RCV) are important to determine whether a population‐based reference interval can be used to detect clinically meaningful changes and facilitate the interpretation of serial measurements. Objective Determine the biological variation of UPC and USG using calculations of RCV and IoI in healthy dogs. Animals Eleven healthy client‐owned young adult dogs. Methods Prospective observational study. First‐morning urine samples were collected by voiding once weekly for 6 consecutive weeks for batch analysis. Twenty random samples were run in duplicate. Urine protein concentration, urine creatinine concentration, and USG were measured using a colorimetric pyrogallol red molybdate complex, enzymatic Jaffe method, and manual refractometer, respectively. Restricted maximum likelihood estimations were used to determine within‐individual, between‐individual, and analytical coefficients of variation and calculation of RCV and IoI. Results All dogs were non‐proteinuric at enrollment (UPC < 0.2) and remained non‐proteinuric on subsequent measurements. Urine protein concentration, urine creatinine concentration, UPC, and USG had intermediate individuality. The RCV was 73% for urine protein concentration, 68% for urine creatinine concentration, 31% for UPC, and 3% for USG. Conclusion Population‐based reference intervals for UPC and USG should be interpreted cautiously for single measurements and calculated RCVs should be applied to serial measurements to identify clinically meaningful changes.